Better Targeting of Inhaled Corticosteroids in Chronic Obstructive Pulmonary Disease - Sonnex, Kimberley (2023)
Introduction: Inhaled corticosteroids (ICS) have long been a treatment option for Chronic Obstructive Pulmonary Disease (COPD). However, questions over their efficacy have persisted and recent changes to guidance have stated that further research is needed to predict the patient factors that indicate ICS responsiveness. The aim of this thesis was to investigate the effect of variables, including smoking status, asthma co-diagnosis and blood eosinophil counts, on the outcomes of COPD with ICS use. Method: Three methodologies were used to investigate the aims of this thesis. Systematic review: To examine the literature on the effect of smoking on outcomes with ICS use in COPD an electronic database search was conducted. Fully published randomised controlled trials, in the English language that stratified the participants by smoking status were included. The primary outcome measures were changes in lung function and yearly exacerbation rates. Random effects panel data model: The Clinical Practice Research Datalink with linkage to Hospital Episode Statistics and Office of National Statistics data were used. The cohort was identified based on a previously validated method by Quint et al (2014). The impact of patient variables on the outcomes of lung function, yearly exacerbations and deaths with COPD after three, five and ten years were investigated. Prospective cohort study: Patients in the cohort above were categorised by yearly ICS usage. Patients prescribed ICS were matched to those not using ICS based on propensity score. The outcomes measured were lung function, yearly exacerbations and deaths after three, five and ten years. Sub-group analysis was performed on the variables of smoking status, asthma co-diagnosis and blood eosinophil levels. Results: Systematic review: Eight studies were identified. Heavier or current smokers did not gain the same benefit from ICS use on lung function and exacerbation rates as lighter or ex-smokers do, however effect size may not be clinically important. Random effects panel data model: An asthma co-diagnosis in people with COPD resulted in a lower probability of death, better lung function and less hospital-treated exacerbations compared to no asthma co-diagnosis. Smoking resulted in reduced lung function and an increased probability of death compared to non-smokers. However, there was no overall effect on yearly exacerbations. Prospective cohort study: ICS use was associated with a greater decline in lung function and increased exacerbation rates but lower probability of death versus no-ICS use. In the sub-group analysis, smoking was associated with an additional 58ml decline in lung function at year five, an increase of 0.074 yearly exacerbations and 6.8% increased probability of mortality with ICS use than for non-smokers. An asthma co-diagnosis conferred decreased probability of mortality of up to 8.2% at year five for ICS users compared to those with no asthma co-diagnosis. ICS use in the high eosinophil group decreased the probability of mortality by 10% at year five compared to non-use. Conclusion: ICS are of some benefit in treating COPD in terms of lung function and exacerbation rates. If they are to be used, targeting them to people with a co-diagnosis of asthma, with high blood eosinophils or are not current smokers will produce the most benefit in terms of decreased probability of death.